The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.memsci.2015.12.060
|View full text |Cite
|
Sign up to set email alerts
|

Robust outer-selective thin-film composite polyethersulfone hollow fiber membranes with low reverse salt flux for renewable salinity-gradient energy generation

Abstract: This study reports outer-selective thin-film composite (TFC) hollow fiber membranes with extremely low reverse salt fluxes and robustness for harvesting salinity-gradient energy from pressure retarded osmosis (PRO) processes. Almost defect-free polyamide layers with impressive low salt permeabilities were synthesized on top of robust polyethersulfone porous supports. The newly developed TFC-II membrane shows a maximum power density of 7.81 W m-2 using 1 M NaCl and DI water as feeds at 20 bar. Reproducible data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 50 publications
(84 reference statements)
1
29
0
Order By: Relevance
“…A similar phenomenon was also suggested as creeping behavior by Chen et al [33]. In addition, Zhang et al [28], Chou et al [20], Wan and Chung [34] and many others [26,27,32,35] observed that the water and salt permeability of TFC HF membranes varied significantly with an increase in hydraulic pressures possibly owing to the microstructure changes of the polyamide layer. However, to the best of our knowledge, there are no systematic and in-depth studies on (1) the micro-deformation of the TFC HF membranes under PRO operations and (2) the effects of the deformation evolution on PRO performance.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…A similar phenomenon was also suggested as creeping behavior by Chen et al [33]. In addition, Zhang et al [28], Chou et al [20], Wan and Chung [34] and many others [26,27,32,35] observed that the water and salt permeability of TFC HF membranes varied significantly with an increase in hydraulic pressures possibly owing to the microstructure changes of the polyamide layer. However, to the best of our knowledge, there are no systematic and in-depth studies on (1) the micro-deformation of the TFC HF membranes under PRO operations and (2) the effects of the deformation evolution on PRO performance.…”
Section: Introductionsupporting
confidence: 56%
“…The innerselective TFC HF membranes are chosen because they currently display much higher power density than the outer selective TFC HF membranes [35][36][37]. The second objective is to examine the effects of micro-deformation on basic permeation properties such as A (water permeability), B (salt permeability) and S (structure parameter).…”
Section: Introductionmentioning
confidence: 99%
“…[28,[44][45][46] Hollow fiber membranes were loaded in the active-facing-draw mode (i.e., the PRO mode) where the active layer faces the draw solution, a synthetic SWRO brine (0.81 mol/L NaCl at pH 5~6). A hydra cell pump (Minneapolis, MN) was used to recirculate the draw solution through the lumen side of the hollow fiber module, and a peristaltic pump (Cole-Palmer, Vernon Hills, IL) was employed to recirculate the feed solution through the shell side of the modules.…”
Section: Membrane Fouling and Cleaning Protocol In Pro Processesmentioning
confidence: 99%
“…Commonly employed approaches include the addition of additives to the casting solutions or coagulations [14,15], the introduction of an extra process [16,17] and chemical modification [18,19].…”
Section: Introductionmentioning
confidence: 99%